2002
DOI: 10.1001/archpedi.156.11.1075
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of the Number and Choice of Leisure Time Physical Activities From Mid to Late Adolescence

Abstract: The decline in PA during adolescence is primarily due to a decrease in the number of activities in which the adolescent is participating, and there is only a moderate probability that an adolescent will continue to participate in an activity during the 4-year period from junior to senior high. Future efforts should be directed at identifying factors associated with initiating and maintaining participation in specific activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
147
4
7

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(183 citation statements)
references
References 21 publications
25
147
4
7
Order By: Relevance
“…Declining levels of physical activity in girls over the transition from childhood to adolescence have been well documented. 23,24 We speculate that girls with a high activity temperament may be better protected from weight gain because their tendency to expend energy is greater. Our cross-sectional observation that girls with a high activity temperament have lower percentage body fat than girls with Figure 2 Adjusted NREE in girls with low activity temperament and girls with high activity temperament stratified by physical activity.…”
Section: Discussionmentioning
confidence: 97%
“…Declining levels of physical activity in girls over the transition from childhood to adolescence have been well documented. 23,24 We speculate that girls with a high activity temperament may be better protected from weight gain because their tendency to expend energy is greater. Our cross-sectional observation that girls with a high activity temperament have lower percentage body fat than girls with Figure 2 Adjusted NREE in girls with low activity temperament and girls with high activity temperament stratified by physical activity.…”
Section: Discussionmentioning
confidence: 97%
“…A longitudinal study verifi ed that the decline in prevalence of physical activity throughout adolescence was primarily due to a decrease in the number of reported physical activities rather than in the time spent in such activities. 1 Thus, engagement in a variety of leisure-time physical activities needs to be encouraged among children and adolescents. In addition, it is important to highlight that physical activity during youth may be a predictor of activity in adult age.…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, PA was significantly correlated with availability of recreational facilities (Gordon-Larsen et al, 2006;Norman et al, 2006), and recreation facilities (both free and commercial) were less available in lower-socioeconomic status (SES) and high-minority areas (Gordon-Larsen et al, 2006). Participation in PAvaries by gender (Gottlieb and Chen, 1985;Bradley et al, 2000;Aaron et al, 2002) and by race/ethnicity (Gottlieb and Chen, 1985;Dowda et al, 2004). Because girls are generally less physically active than boys, it is particularly important to understand the role the environment plays in promoting or discouraging their PA.…”
Section: Introductionmentioning
confidence: 99%
“…Because girls are generally less physically active than boys, it is particularly important to understand the role the environment plays in promoting or discouraging their PA. Girls may not be aware of community facilities, or may not find activities that are affordable or of interest to them (Dunton et al, 2003;Centers for Disease Control and Prevention, 2003) Activities commonly engaged in by girls, such as dance, aerobics, bowling, roller skating, and swimming (Gottlieb and Chen, 1985;Bradley et al, 2000;Aaron et al, 2002;Dowda et al, 2004) typically take place in commercial facilities, and using these venues have been shown to be correlated with middle school girls' PA in several studies (Norman et al, 2006;Hoefer et al, 2001). In one study, 48% of parents of 9-to 13-year-old girls reported that cost was a barrier to PA (Centers for Disease Control and Prevention, 2003).…”
Section: Introductionmentioning
confidence: 99%